Intraoperative Micro-Doppler in Cerebral Arteriovenous Malformations - Burkhardt, Till; Siasios, Giannis; Schmidt, Nils Ole; Reitz, Mathias; Regelsberger, Jan; Westphal, Manfred (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Introduction Intraoperative micro-Doppler (IOMD), intraoperative digital substraction angiography (DSA), and microscope-integrated indocyanine green angiography are methods that guide neurosurgical resection of arteriovenous malformations (AVMs) in the brain and minimize the trauma of healthy tissue. In this study we emphasize the use of IOMD in AVM surgery, analyzing the advantages and the limitations of this method.Patients and Methods A total of 32 patients were diagnosed with an AVM. Supplying arteries and draining veins were analyzed regarding hemodynamic profiles, flow velocities, pulsatility index (PI), and resistance index (RI). Venous drainages were accompanied by arterial blood flow disturbances that showed typical characteristics in all cases. We set an angle of 60 degrees between the examined vessel and the probe to achieve a more reliable and comparable measurement. Postoperative DSA was performed in all patients.Results Supplying arterial blood vessels of AVMs could be identified by their characteristic blood flow profiles with PI < 0.7 and RI < 0.55. Drainage veins in all 32 cases showed normalized venous flow patterns without arterial flow turbulences at the end of the surgical procedure. Postoperative DSA revealed a residual AVM in one patient.Conclusions IOMD constitutes a safe, accurate, and low-cost imaging modality for evaluating blood flow velocities and for optimal stepwise AVM elimination without unnecessary sacrifice of veins. PI and RI are reliable parameters in diagnosing cerebrovascular malformations, but systolic and diastolic flow velocities may vary to a greater extent. This phenomenon has never been elucidated previously and therefore needs to be emphasized when using this technique intraoperatively.
Keywords: arteriovenous malformation; micro-Doppler; intraoperative; vascular